A Digital Esthetic Rehabilitation of a Patient with Dentinogenesis Imperfecta Type II: A Clinical Report. Issue 8 (10th September 2020) - Shi, Shi; Li, Ning; Jin, Xiaoting; Huang, Shengbin; Ma, Jianfeng
Abstract: A 19‐year‐old female affected by dentinogenesis imperfecta type II (DI‐II), a genetic disease that affects the structural integrity of the dentin, presented with a chief complaint of discolored teeth. For this patient, digital techniques, including digital smile design (DSD), the ARCUSdigma axiograph and computer‐aided design/computer‐aided manufacturing (CAD/CAM), were extensively used in all phases of the rehabilitation process. Compared to traditional analog methods, these digital techniques could reduce the constant confirmation of occlusion, promote communication between clinicians and dental technicians, achieve accurate occlusion with relatively high efficiency, and improve the efficacy of esthetic rehabilitation in the treatment of this patient with DI‐II.